1965
DOI: 10.1002/pol.1965.100031215
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the association of poly(methacrylic acid) with divalent cations on the stereoregularity of the polymers

Abstract: The complexation of Cu2+ and Mg2+ with isotactic and syndiotactic poly(methacrylic acid) was studied by dialysis equilibrium over a range of degrees of ionization of the polymeric acid. It was found that the isotactic polymer has the higher affinity for Cu2+, while Mg2+ is bound more strongly to the syndiotactic species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Therefore, the monomers approach in a sterically more favorable syndiotactic-like mode. It is worth recalling that PMMA chains formed in toluene at low temperature without any additive are rich in isotactic triads (mm ∼ 60%). Under these polymerization conditions, multiple active species are commonly formed and side reactions make the molecular weight distribution (MWD) quite broad. Hatada et al , have reported that t-C 4 H 9 MgBr prepared in diethyl ether causes no side reaction in the polymerization of MMA in toluene at −78 °C and forms highly isotactic polymer (mm > 95%) with rather narrow MWD ( M̄ w / M̄ n < 1.2).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the monomers approach in a sterically more favorable syndiotactic-like mode. It is worth recalling that PMMA chains formed in toluene at low temperature without any additive are rich in isotactic triads (mm ∼ 60%). Under these polymerization conditions, multiple active species are commonly formed and side reactions make the molecular weight distribution (MWD) quite broad. Hatada et al , have reported that t-C 4 H 9 MgBr prepared in diethyl ether causes no side reaction in the polymerization of MMA in toluene at −78 °C and forms highly isotactic polymer (mm > 95%) with rather narrow MWD ( M̄ w / M̄ n < 1.2).…”
Section: Introductionmentioning
confidence: 99%
“…Special types of polyelectrolytes are commonly employed in municipal sewage treatments for flocculation purposes. During the present work the precipitation of several polyelectrolytes (samples PE 13,17,30,35, 43,47, and 49) was observed at pH 6-7 when they were titrated with 0.01 N CaCl2 solution. Lang et al reported the water insolubility of Li and Ba salts of poly(maleic acid) (13).…”
Section: Introductionmentioning
confidence: 67%
“…213,214 In addition, we note that chelation of adjacent carboxylate groups of ionized poly(methacrylic acid) has been used to rationalize the dependence of metal binding affinities on tacticity. Studies by Morawetz, 215 Morcellet, 216 and Bello 217 have demonstrated that the metal binding affinities have a significant tacticity dependence, which the authors attribute quite intuitively to 8-membered chelation of adjacent carboxylate (or carboxylic acid) side-chains. Collectively, these studies indicate that the relatively poor stereocontrol obtained in radical polymerization is probably not attributable solely to low selectivity for the larger chelate complexes, although this may be responsible for some of the variation in the effectiveness of LAs.…”
Section: Is the Chelate Unstable?mentioning
confidence: 97%